Preservation, Radicalism, and the Avant-Garde Canon - Ferreboeuf, Rebecca; Noble, Fiona; Plunkett, Tara.; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
Preservation, Radicalism, and the Avant-Garde Canon interrogates the contemporary significance of the avant-garde. The contributors question the role of academia and exhibition cultures in redefining, reshaping, preserving, and transmitting the products of this historical phenomenon. Such contemporary scholarly and exhibition-based exploration institutionalizes avant-garde productions and, in doing so, threatens the potency of the avant-garde which relies on its marginal position. This volume brings together case studies to examine what constitutes the avant-garde canon.
Keywords: Motion pictures-History.; Performing arts; Literature-Philosophy.; Theater-History.; Fine Arts; Film History